T lymphocyte cell epitopes prediction of newcastle disease virus isolated from pigeon (Columba livia domestica) - Rahmahani, Jola; Abdul Rantam, Fedik; Regilya Fatimah, Tetri; Hanny Irawan, Anastasia; Putri, Naimah; Hendrianto, Eryk (Research journal of pharmacy and technology, 2024)
Newcastle disease is a viral disease that occurs annually in poultry farms in Indonesia. It is caused by infection of avian paramyxovirus serotype 1. It infects many types of birds, including pigeons, ostriches, waterfowl, chickens and parrots. Controls such as vaccination, did not protect poultry from infection with Newcastle disease virus (NDV). It should be noted that the protective efficacy of seed vaccines is affected by epitopes that produce different levels of protective efficacy in vaccination regimens. Subunit vaccines might be the best choice for preventing NDV infection. Pigeon (Columba livia Domestica) samples were collected at a live bird market in Surabaya. Collected samples showed clinical signs such as respiratory distress, limp, anorexia, and subclinical bowel/diarrhea. A molecular approach was taken to obtain the nucleotide sequences of the samples. Molecular analysis was performed to obtain B-cell epitopes that can safely induce the immune system. This sequence was used for T lymphocyte cell epitope analysis using EIDB. The obtained epitopes were analyzed with Vaxijen, Allertop and ToxinPred and confirmed to be safe to use. Peptides were obtained from her NDV-infected pigeons identified as potential seed vaccine candidates. Some peptides such as GSWVYIHLLSTFTLL, PYMVVRLRRSLNTCKL, NWQLSLRPYMVVRLR, RASLANLYPAAFSVF were obtained from Pigeon/Surabaya/2019/03, while Pigeon/Surabaya/2019/01 produced some peptides, but the required characteristics did not meet. These epitopes may be used as subunit vaccines to eradicate Newcastle disease virus.